Analisis Kompetensi Pedagogik Pendidik PAUD dalam Pengembangan Pembelajaran - Erna Roostin; Muhammad Syarif Sumantri; Nurbiana Dhieni (Eduprof : Islamic Education Journal, 2022)
Pedagogy is the study of how to educate and guide children according to their development. Pedagogic competence is basically the ability of teachers to manage student learning and the distinctive competencies that will distinguish teachers from other professions will also determine the level of success of the process and learning outcomes of their students. The purpose of this study was to determine and analyze the pedagogic competencies possessed by early childhood educators in developing learning in early childhood education programs. The method used in this research is a descriptive qualitative approach with a literature review method, data collection techniques carried out by researchers are the results of previous studies in the form of Scopus indexed international journals and National journals with a reputation for Sinta 2 and relevant to the research topic. The data analysis technique used is content analysis. The findings from the data analysis showed that the pedagogic competence of educators includes the implementation of further learning, namely the achievement of learning objectives which means that the learning that has been designed by educators is able to develop aspects of child development such as religious and moral values, physical-motor, language, cognitive, art, and social-emotional as outlined through the learning objectives. Quality educators are educators who have many abilities, especially in terms of teaching and learning, therefore educators need to develop their quality by continuing to hone their abilities. ABSTRAK Pedagogik ilmu yang mempelajari tentang bagaimana mendidik dan membimbing anak sesuai dengan perkembangannya. Kompetensi Pedagogik pada dasarnya kemampuan guru dalam mengelola pembelajaran peserta didik dan kompetensi khas yang akan membedakan guru dengan profesi lainnya juga akan menentukan tingkat keberhasilan proses dan hasil pembelajaran peserta didiknya. Tujuan penelitian ini untuk mengetahui dan menganalisis kompetensi pedagogik yang dimiliki oleh pendidik anak usia dini dalam mengembangkan pembelajaran di PAUD. Metode yang digunakan dalam penelitian ini pendekatan kualitatif deskriptif dengan metode studi literatur (literature review), teknik pengumpulan data yang dilakukan oleh peneliti yaitu hasil penelitian terdahulu berupa jurnal internasional terindeks scopus dan jurnal Nasional yang bereputasi sinta 2 serta relevan dengan topik penelitian. Teknik analisis data yang digunakan adalah analisis isi (content analysis). Hasil temuan dari analisis data diperoleh bahwa kompetensi pedagogik pendidik meliputi pelaksanaan pembelajaran selanjutnya yaitu ketercapaiannya tujuan pembelajaran yang mengandung arti bahwa pembelajaran yang telah dirancang oleh pendidik mampu mengembangkan aspek perkembangan anak seperti nilai agama dan moral, fisik-motorik, bahasa, kognitif, seni, dan sosial-emosional yang dituangkan melalui tujuan pembelajaran. Pendidik yang berkualitas adalah pendidik yang memiliki banyak kemampuan khususnya dalam hal belajar mengajar, oleh karena itu pendidik perlu mengembangkan kualitasnya dengan terus mengasah kemampuannya.